2010
DOI: 10.1098/rspb.2010.0831
|View full text |Cite
|
Sign up to set email alerts
|

Within-host competition selects for plasmid-encoded toxin–antitoxin systems

Abstract: Toxin-antitoxin (TA) systems are commonly found on bacterial plasmids. The antitoxin inhibits toxin activity unless the system is lost from the cell. Then the shorter lived antitoxin degrades and the cell becomes susceptible to the toxin. Selection for plasmid-encoded TA systems was initially thought to result from their reducing the number of plasmid-free cells arising during growth in monoculture. However, modelling and experiments have shown that this mechanism can only explain the success of plasmid TA sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…Many of GGI encoded genes show similarity to those from the Escherichia coli F-plasmid conjugation system and, the order of the genes in the GGI is highly similar to the IncF family of conjugative plasmids, consistent with the GGI being an ancestral chromosomally inserted plasmid 17, 40. In particular, the DNA methylases, ydg (NEIS2288) and ydhA (NEIS2289) can be found which may enable within host competition between plasmids consistent with the low prevalence of isolates here possessing both a plasmid and the GGI 41 (Supplementary Tables 1 and 4). …”
Section: Discussionsupporting
confidence: 70%
“…Many of GGI encoded genes show similarity to those from the Escherichia coli F-plasmid conjugation system and, the order of the genes in the GGI is highly similar to the IncF family of conjugative plasmids, consistent with the GGI being an ancestral chromosomally inserted plasmid 17, 40. In particular, the DNA methylases, ydg (NEIS2288) and ydhA (NEIS2289) can be found which may enable within host competition between plasmids consistent with the low prevalence of isolates here possessing both a plasmid and the GGI 41 (Supplementary Tables 1 and 4). …”
Section: Discussionsupporting
confidence: 70%
“…ParD-ParE toxin-antitoxin systems are commonly found in bacterial plasmids and chromosomes of Gammaproteobacteria and Alphaproteobacteria (53)(54)(55), and plasmids harboring both TA systems and antibiotic resistance genes are widely distributed in enterococci (24,56). However, to the best of our knowledge, pEMB1 is the first plasmid harboring a ParD-ParE TA system and an ampicillin resistance gene identified from human-influenced (wastewater sludge) and pristine (remote mountain soil) environments.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that, in a homogeneous environment, colicin-producing Escherichia coli genotypes prevent invasion by colicin-sensitive genotypes, and vice-versa (7). Toxin-antitoxin addiction systems have been described in X. fastidiosa (29,30), and their role in the ecology of this bacterium should be considered (15).…”
Section: Discussionmentioning
confidence: 99%